Response of Various Nitrogen Levels on the Growth and Yield Performance of Tomato (Lycopersicon Esculentum Mill.) - Qadir Bux Baloch; Altaf Hussain; Niaz Ahmed Wahocho; Nasir Ali Baloch; Safdar Ali Wahocho; Arshad Ali Kaleri; Rameez Raja Kaleri; Abdul Qadir Gola (Journal of Basic & Applied Sciences, 2017)
Nitrogen (N) fertilization at optimum quantity to cultivated plants is essential for sustainable crop productivity. The experiment was conducted to evaluate the response of nitrogen fertilizers on the growth and yield traits of tomato during 2016, at the experimental field of Orchard, | department of Horticulture, Sindh Agriculture University Tandojam. Six nitrogen treatment doses were tested (T1 =control (untreated), T2 = 30 N kg ha-1, T3 = 60 N kg ha-1, T4 = 90 N kg ha-1, T5 = 120 N kg ha-1 and T6 = 150 N kg ha-1.). The data were recorded on the number of branches plant-1, days to flowering, days to fruiting, number of fruits plant-1, weight of single fruit (g), yield plot-1 and yield ha-1 (tons). The results demonstrated that N fertilization showed significant influence on both vegetative and reproductive traits of tomato. On the contrary, plants which were not fertilized with N displayed minimum values for all investigated traits. The highest N level (150 kg ha-1) showed maximum number of branches (5.51) plant-1, minimum day to flowering (42.43) less days to fruiting (46.00), more fruits plant-1 (31.00) maximum weight of single fruit (46.50 g) and highest fruit yield plot-1 (21.01 kg) and per hectare (14008 tons), respectively. It was concluded that the crop growth and productivity was significantly influenced by various levels of nitrogen. However, 150 N kg ha-1 as compared to 120 N and other concentrations considerably displayed better performance in terms of vegetative and reproductive traits of tomato. Hence for optimum growth and economically higher yield, the tomato crop may be fertilized with 150 N kg ha-1.